Sharia Dynamics : Islamic Law and Sociopolitical Processes - Daniels, Timothy P. (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This multidisciplinary volume explores the role of Islamic law within the dynamic processes of postcolonial transformation, nation building, and social reform. Here, eleven international scholars examine Islamic law in several contemporary sociopolitical contexts, focusing specifically on Malaysia, Indonesia, Pakistan, China, Tunisia, Nigeria, the United States, and the International Islamic Fiqh Academy (IIFA) of the Organization of Islamic Cooperation (OIC). The contributors also address the entanglement of Islamic law and ethics with the history of Muslim religious discourses, shifts toward modernity, gender relations, and efforts to construct exclusive or plural national communities. Sharia Dynamics, at once enchanting and enlightening, is a must-read for scholars of contemporary Islam. .
Keywords: Social sciences.; Islam.; Religion and sociology.; Ethnology.; elektronické knihy; electronic books